CRISPR-Cas9-Mediated Single-Gene and Gene Family Disruption in Trypanosoma cruzi - Duo Peng (American Society for Microbiology, 2015)
ABSTRACT Trypanosoma cruzi is a protozoan parasite of humans and animals, affecting 10 to 20 million people and innumerable animals, primarily in the Americas. Despite being the largest cause of infection-induced heart disease worldwide, even among the neglected tropical diseases (NTDs) T. cruzi is considered one of the least well understood and understudied. The genetic complexity of T. cruzi as well as the limited set of efficient techniques for genome engineering contribute significantly to the relative lack of progress in and understanding of this pathogen. Here, we adapted the CRISPR-Cas9 system for the genetic engineering of T. cruzi, demonstrating rapid and efficient knockout of multiple endogenous genes, including essential genes. We observed that in the absence of a template, repair of the Cas9-induced double-stranded breaks (DSBs) in T. cruzi occurs exclusively by microhomology-mediated end joining (MMEJ) with various-sized deletions. When a template for DNA repair is provided, DSB repair by homologous recombination is achieved at an efficiency several orders of magnitude higher than that in the absence of CRISPR-Cas9-induced DSBs. We also demonstrate the high multiplexing capacity of CRISPR-Cas9 in T. cruzi by knocking down expression of an enzyme gene family consisting of 65 members, resulting in a significant reduction of enzymatic product with no apparent off-target mutations. Lastly, we show that Cas9 can mediate disruption of its own coding sequence, rescuing a growth defect in stable Cas9-expressing parasites. These results establish a powerful new tool for the analysis of gene functions in T. cruzi, enabling the study of essential genes and their functions and analysis of the many large families of related genes that occupy a substantial portion of the T. cruzi genome. IMPORTANCE Trypanosoma cruzi, the causative agent of human Chagas disease, is the leading worldwide cause of infectious myocarditis. Diagnostics for the infection are relatively poor, treatment options are limited and of variable effectiveness, and suitable vaccines are nonexistent. The T. cruzi genome is replete with genes of unknown function and greatly expanded gene families with hundreds of members. The absence of facile genetic engineering tools, including RNA interference, for T. cruzi has prevented elucidation of gene and gene family function and the development of better infection prevention and control measures. In this study, we demonstrate that the CRISPR-Cas9 system is a versatile and powerful tool for genome manipulations in T. cruzi, bringing new opportunities for unraveling the functions of previously uncharacterized genes and how this human pathogen engages its large families of genes encoding surface proteins to interact with human and animal hosts.